Sediment routing in bedrock-controlled channels - Odiyo, John Ogony (My University, 2007)
A sediment budget model in which each steady discharge scours sediment along a trajectory towards ultimate target storage or deposits sediment towards the same ultimate target storage has been conceptualized and developed. The method is aimed at routing sediment in morphologically diverse bedrock-controlled channels in which sediment transport and storage is not a continuous process in space and time and mostly occurs in response to discrete discharges. The relative value of the ultimate stable scour depth (Huss) for each steady discharge with respect to the current scour depth after adding sediment supply determines the potential to scour or store sediment. Scour depths measured at discrete locations along the longitudinal profile of a laboratory pool at discrete times until changes in scour were not discernible for each steady discharge and sediment size have been integrated to provide the Huss and storage depletion curve. The experimentally established dependence of scour depth on critical flow depth, settling velocity and sediment supply formed the basis of generating dimensionless Huss and storage depletion curve from these parameters using the Buckingham π theorem. The optimization of experimental results to generate the storage depletion curve gave the exponent of time (φ) and the exponential decay factor (k) as 0.5 and 0.0040207 respectively. Regression fit of dimensionless Huss and critical flow intensity gave a linear relationship with a gradient of 0.90214, y-intercept of –1.4766 and R2 of 96%. The suitability of the model for budgeting sediment dynamics in a series of connected storage units, the validity of using the relative values of Huss and the current scour depth after adding sediment supply to determine scour potential and the existence of active storage associated with sediment supply for each steady discharge have been confirmed experimentally. Modelling with equivalent steady discharges computed from unit stream power principles on the rising and the falling limbs of the hydrograph resulted in scour on the rising limb of magnitude dependent on the magnitude and sequence of the flood event, and less or no scour on recession. The modelling concepts and approach have thus been validated and the potential to reasonably simulate sediment storage changes in bedrock-controlled rivers demonstrated.
Student Number : 9700136A - PhD thesis - School of Civil and Environmental Engineering - Faculty of Engineering and the Built Environment
Keywords: Bedrock-controlled channels; sediment routing; scour depth; active storage